Estudio de cargabilidad del sistema de subtransmisión a 69kv Ambato – Latacunga para determinar las condiciones de operación. - Mise Guanoluisa, Carlos Danilo (2022)
In the present research work, a chargeability analysis of the 69kV Ambato - Latacunga subtransmission line was carried out to determine the operating conditions such as voltage levels and power factor in each bar and comparing its current state with the ARCONEL regulations. 053 / 18 where it was verified if their values are within the levels established by this regulation, for which the modeling of the electrical system was carried out with the help of the Digsilent power factory software and through simulations it was determined that it is happening when conditions occur. At maximum, average and minimum demand, the voltage variation and the power factor do not comply with the limits established in the regulations, for which the analysis was carried out of what mitigation measures for voltage collapse problems can be suggested to improve the profiles. of voltage as well as the type and power of SVC that should be installed to automatically compensate the factor of power.